2012
DOI: 10.1016/j.neuroimage.2011.12.067
|View full text |Cite
|
Sign up to set email alerts
|

Fighting food temptations: The modulating effects of short-term cognitive reappraisal, suppression and up-regulation on mesocorticolimbic activity related to appetitive motivation

Abstract: The premise of cognitive therapy is that one can overcome the irresistible temptation of highly palatable foods by actively restructuring the way one thinks about food. Testing this idea, participants in the present study were instructed to passively view foods, up-regulate food palatability thoughts, apply cognitive reappraisal (e.g., thinking about health consequences), or suppress food palatability thoughts and cravings. We examined whether these strategies affect self-reported food craving and mesocorticol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
135
1
8

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(157 citation statements)
references
References 53 publications
13
135
1
8
Order By: Relevance
“…For example, exposure to real food results in more craving in people with bulimic disorders than HCs [49]. Within-paradigm assessments of food craving in HCs showed increased craving only when people were instructed to think about the palatability of the food, but not in other conditions [47]; this supports the idea that the instruction that we used was more complex and may have resulted in suppression of urges to eat the food in both healthy and BN participants.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…For example, exposure to real food results in more craving in people with bulimic disorders than HCs [49]. Within-paradigm assessments of food craving in HCs showed increased craving only when people were instructed to think about the palatability of the food, but not in other conditions [47]; this supports the idea that the instruction that we used was more complex and may have resulted in suppression of urges to eat the food in both healthy and BN participants.…”
Section: Discussionsupporting
confidence: 59%
“…While no study has directly investigated this ‘instruction’ effect in a within-subject comparison in people with an eating disorder, Siep et al (2012) have demonstrated that brain activation in frontal and striatal regions can differ based on the instructions given, e.g. 1) to passively view foods, 2) to up-regulate food palatability thoughts, 3) to apply cognitive reappraisal (e.g., thinking about health consequences), or 4) suppress food palatability thoughts and cravings [47]. An indirect comparison with their findings suggests that the left medial prefrontal cortex activation seen in both our HC and BN group (Table 2) is in accord with the task to ‘up-regulate’ food palatability.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, when participants in Siep et al (2012) were asked to suppress any thoughts about food palatability and food craving, they showed decreased neural activity in the ventral reward pathway (e.g. ventral striatum), together with enhanced activity in regulatory areas (e.g.…”
Section: Modulations Of the Core Eating Network Associated With Eatinmentioning
confidence: 99%
“…Siep et al (2012) demonstrated the neural consequences of focusing on hedonic pleasure. When participants were asked to focus on the hedonic properties of highly palatable foods (smell, taste, and texture) in the up-regulation condition, they exhibited increased food craving and enhanced activation in the ventral reward pathway (ventral striatum, ventral tegmental area, operculum, insula, mOFC, and vmPFC).…”
Section: Modulations Of the Core Eating Network Associated With Eatinmentioning
confidence: 99%
“…1). Finally, the use of cognitive reappraisal strategies has been shown to regulate appetitive responses to highly palatable foods via these same neural systems (Kober et al, 2010; Hollmann et al, 2012; Siep et al, 2012; Yokum and Stice, 2013). …”
Section: Non-invasive Neuromodulation Approaches: Recent Developmentsmentioning
confidence: 99%